2022
DOI: 10.1111/hiv.13413
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and diabetes in people of African ancestry with HIV

Abstract: Obesity is a chronic disease with multiple adverse effects on health. The prevalence of obesity is increasing worldwide, and people of African ancestry are disproportionally affected. Several widely used antiretrovirals have been associated with weight gain and contribute to the rising burden of obesity in people with HIV.Obesity and weight gain on antiretroviral therapy are risk factors for the development of type 2 diabetes mellitus, a condition which also disproportionally affects black populations. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Several studies have suggested that the modern ART regimens may be the major contributing cause of increasing obesity [1,2,21]. Indeed, WWH experience weight gain with ART initiation, and this weight gain is greater compared to men in several studies [1,12,21,22]. Integrase strand-transfer inhibitor (INSTI)-based ART, specifically, has been associated with increased weight gain especially among WWH [1,2,21,23].…”
Section: Contributors To Obesitymentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have suggested that the modern ART regimens may be the major contributing cause of increasing obesity [1,2,21]. Indeed, WWH experience weight gain with ART initiation, and this weight gain is greater compared to men in several studies [1,12,21,22]. Integrase strand-transfer inhibitor (INSTI)-based ART, specifically, has been associated with increased weight gain especially among WWH [1,2,21,23].…”
Section: Contributors To Obesitymentioning
confidence: 99%
“…In contrast, those with greater food insecurity may have lower levels of ART adherence, resulting in higher viral loads, and periods of chronic hunger followed by an increased compensatory consumption of food leading to a 'thrifty phenotype' in future generations [8,30,31]. Lastly, cultural perceptions of a 'healthy' weight may differ considerably among WWH, particularly in many African communities where higher weight may be perceived as more common among people without HIV, persons of greater prosperity, and persons in better health [8,9,[11][12][13]18].…”
Section: -630xmentioning
confidence: 99%
See 3 more Smart Citations